Genomic gains in prostatic carcinoma and proliferative inflammatory atrophy in dogs - Alves, Carlos Eduardo Fonseca [UNESP]; Busso, Ariane Fidelis; Silveira, Sara M.; Rogatto, Silvia Regina [UNESP]; Amorim, Renee Laufer [UNESP] (My University, 2012)
The dog can spontaneously develop prostate cancer and consequently can be used as an experimental model for prostatic diseases associated with aging, including benign prostate hyperplasia (BPH) and prostate carcinoma (PCa). DNA copy number variations (CNVs) have been used to identify genes associated with cancer development and progression. DNA microarray based comparative genomic hybridization (aCGH) is a technique that allows to identify copy number of thousands of genes throughout the genome. aCGH was used to identify genomic regions with significantly different DNA copy number in three benign prostatic hyperplasia (BPH), four proliferative inflammatory atrophy (PIA), and 14 canine prostate carcinoma (PCa). Five histologically normal prostate tissue were used as reference. Genomic DNA was extracted from formalin fixed and paraffin embedded samples and CNVs data was evaluated in Canine Genome CGH Microarray 4x44K (G2519F, Design ID021193, Agilent). Data analysis was performed using Genomic Workbench Standard Edition 5.0.14 (Agilent). PCa showed higher number of altered genes related to canonical diseases process, cellular functions and molecular pathways as well as greater inter-relationship between genes, compared with PIA and BPH. In conclusion, PCa showed a more complex genotype, being losses the most frequent genomic changes. Some discrepancies between genomic alterations in human and canine carcinomas may indicate the different clinical behavior of these tumors in these two species. In addition, it was observed was an ascending pattern of genomic complexity in BPH, PIA and CA consistent with a model of multistep tumor progression.